Efektivitas Metode Pembelajaran Continuity Of Care Terhadap Peningkatan Kompetensi Pemberian Asuhan Kebidanan - Purwaningtias Budi Utami; Irfan Irfan; Siti Noorbaya (Indonesian Journal of Midwifery (IJM), 2020)
Postpartum, also called the puerperium or puerperium, is the time since the baby is born and the placenta is separated from the uterus until the next 6 (six) weeks, accompanied by the recovery of the organs associated with the womb, which have undergone changes related to childbirth. The changes that occur during the puerperium include all systems including the reproductive organs such as the uterus and vulva, from physiological to pathological changes as a result of complications during the puerperium. Complications of the puerperium are abnormal conditions during the puerperium caused by the entry of germs to the genetalia during labor and the puerperium, one of the complications of the puerperium, namely a rupture, is also called a perineal tear or laceration. This study aims to analyze the effectiveness of giving boiled snakehead fish on the healing of perineal lacerations in postpartum mothers in Samarinda City. In this study, the authors used a quasi-experimental method with a post-test only control group design in which the measurement of variables was given a special intervention, namely giving 100 g of steamed fish a day for 10 days, then observing its effect on post-partum maternal wound healing. As a comparison, also a control group without treatment with inclusion and exclusion criteria. The research location is at Kartika Jaya Clinic, Samarinda City. In this study, the samples were selected using purposive sampling. Data collection methods used in two ways, namely through interviews and observations. The test used Mann Whitney. The results of data analysis using the Mann-Whitney obtained the sig (2-tiled) value of 0.000 <0.05 with the average healing time of the experimental group was 7 days. Meanwhile, the average healing time for the control group was 10 days. So it can be concluded that there is an effect of giving steamed cork fish on the healing of perineal lacerations in postpartum mothers with a difference of 3.2 days. The conclusion of this study is that the administration of steamed snakehead fish is more effective in treating perineal lacerations of postpartum mothers. Student competency results obtained through the pre-test and post-test showed that the difference between the pre-test and the final test for the two groups was significantly different. This is indicated by the results of the t test obtained by t count = 0.001 <t table = 0.05, which means that H0 is rejected. With the rejection of H0, this means that the results of student competence in providing midwifery care using the Continuity of Care learning method are better than those using the ordinary practicum method. The difference in competency results between the control class and the experimental class occurs because the experimental class uses Continuty of Care learning and the control class uses the ordinary practicum method